Evaluation of workload among Board-Certified Psychiatric Pharmacists in the United States - Kelly C. Lee, PharmD, MAS, BCPP, FCCP, FASHP; Samantha Catanzano, PharmD, BCPP; Melissa Mooers Gross, BS, PharmD, MHA, BCPP, BCPS, BCGP, BCIDP, CPEL, CPPS; Monica Fahmy, PharmD, BCPP, BCPS; Jennifer N. Gemmellaro, PharmD, BCPP, BCPS; Gregory H. Payne, MBA, CAE (Mental Health Clinician)
Introduction Board-Certified Psychiatric Pharmacists (BCPPs) are highly trained mental health providers. The workload of clinical pharmacists has been inconsistently reported in the literature. The goals of this study were to quantify the typical and ideal workloads of BCPPs and characterize their practice settings and clinical activities. Methods This was a cross-sectional survey study of BCPP members of the American Association of Psychiatric Pharmacists. The survey included demographic, practice-related, and burnout questions. The primary outcome was the self-reported typical and ideal workloads of BCPPs in inpatient, outpatient, and transition-of-care settings. Secondary outcomes included practice settings and types of activities. Results Of 571 invitees, 173 respondents were included in the analysis. The mean typical number of patients per day for inpatient and outpatient BCPPs were 35.6 (±22.8) and 9.29 (±10.9), respectively. The mean ideal number of patients per day for inpatient and outpatient BCPPs were 23.6 (±10.4) and 9.96 (±10.6), respectively. Inpatient pharmacists reported spending 15.4 (±12.2) hours on direct patient care and consults during a typical workweek compared with outpatient pharmacists (25.4 ± 15.1, p ≤ .001). A greater number of outpatient pharmacists reported that electronic health record documentation contributed to a significant portion of their workflow compared with inpatient pharmacists (96.2% versus 71.9%, respectively, p ≤ .001). Discussion This was the first study to quantify BCPPs self-reported typical and ideal workload in different practice settings. Future research is needed to identify the factors that determine ideal workloads for BCPPs at specific practice sites.